Strategies of Early Childhood Teachers in Developing School Readiness - Hanifah, Siti; Basyiroh, Iis; Hikmah, Dede (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
This study aims to analyze early childhood teachers’ strategies in managing classrooms to foster school readiness during the transition to primary school. The participants consisted of four early childhood education (ECE) teachers in Purwakarta Regency. Data were collected through in-depth interviews, classroom observations, and documentation, and analyzed using Braun and Clarke’s thematic analysis model. The findings reveal that teachers employed various strategies, including routine habituation, play-based learning, and the reinforcement of socio-emotional skills. Challenges encountered include limited facilities, diverse levels of children’s readiness, and insufficient collaboration with parents and primary schools. A critical analysis using Paulo Freire’s framework highlights the importance of participatory and transformative approaches in supporting children’s transitions. The study emphasizes that school readiness encompasses not only academic aspects but also socio-emotional development and the support of a holistic educational ecosystem. The novelty of this research lies in its focus on teachers’ classroom practices in building school readiness, offering valuable insights for the development of early childhood education practices and policies in Indonesia.